Storia delle telecomunicazioni - CANTONI, VIRGINIO; FALCIASECCA, GABRIELE; Pelosi, Giuseppe (Firenze University Press, 2011)
Focusing on the history of scientific and technological development over recent centuries, the book is dedicated to the history of telecommunications, where Italy has always been in the vanguard, and is presented by many of the protagonists of the last half century. The book is divided into five sections. The first, dealing with the origins, starts from the scientific bases of the evolution of telecommunications in the nineteenth century (Bucci), addressing the developments of scientific thought that led to the revolution of the theory of fields (Morando), analysing the birth of the three fundamental forms of communication - telegraph (Maggi), telephone (Del Re) and radio (Falciasecca) - and ending with the contribution made by the Italian Navy to the development of telecommunications (Carulli, Pelosi, Selleri, Tiberio). The second section, on technical and scientific developments, presents the numerical processing of signals (Rocca), illustrating the genesis and metamorphosis of transmission (Pupolin, Benedetto, Mengali, Someda, Vannucchi), network packets (Marsan, Guadagni, Lenzini), photonics in telecommunications (Prati) and addresses the issue of research within the institutions (Fedi-Morello), dwelling in particular on the CSELT (Mossotto). The next section deals with the sectors of application, offering an overview of radio, television and the birth of digital cinema (Vannucchi, Visintin), military communications (Maestrini, Costamagna), the development of radar (Galati) and spatial telecommunications (Tartara, Marconicchio). Section four, on the organisation of the services and the role of industry, outlines the rise and fall of the telecommunications industries in Italy (Randi), dealing with the telecommunications infrastructures (Caroppo, Gamerro), the role of the providers in national communications (Gerarduzzi), the networks and the mobile and wireless services (Falciasecca, Ongaro) and finally taking a look towards the future from the perspective of the last fifty years (Vannucchi). The last section, dealing with training and dissemination, offers an array of food for thought: university training in telecommunications, with focus on the evolution of legislation and on the professional profiles (Roveri), social and cultural aspects (Longo and Crespellani) as well as a glance over the most important museums, collections and documentary sources for telecommunications in Italy (Lucci, Savini, Temporelli, Valotti). The book is designed to offer a compendium comprising different analytical approaches, and aims to foster an interest in technology in the new generations, in the hope of stimulating potentially innovative research.